ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN TERBUKA DI JAWA TIMUR 2012-2022 - Kerina Della Puspita; Moh. Athoillah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
East Java Province has the second population density after West Java Province. This number of population can certainly be an advantage with abundant human resources or problems related to employment. This research is to find out and analyze the effect of minimum wages, population, HDI, PMTB, economic growth, and the agricultural sector has an open response rate in 38 districts/cities of East Java Province in 2012-2022. This study uses quantitative research with panel data models. The results of the research show that the data is free from classical assumption problems with the minimum wage variable having a significant positive influence, the population variable and the agriculture, forestry and fisheries variables having an insignificant and positive influence, the HDI and PMTB variables having a significant negative influence, the economic growth variable having the influence is insignificant and negative.